2019
DOI: 10.1021/acs.jpcc.9b04379
|View full text |Cite
|
Sign up to set email alerts
|

Size Effects in Nanocrystalline Thoria

Abstract: The facile chemical precipitation method and subsequent thermal treatment were shown to be suitable for preparation of crystalline ThO2 nanoparticles (NPs) in a wide range of particle sizes (from 2.5 to 34.3 nm). The obtained NPs were investigated with X-ray diffraction, high-resolution transmission electron microscopy and X-ray absorption techniques to find out the possible size effects associated with nanocrystalline thoria. For 2.5 nm NPs, the lattice parameter of ThO2 was found to increase by up to 1.1 %, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 86 publications
10
60
0
Order By: Relevance
“…Carbonate and hydroxyl surface groups have been suggested to exhibit a tensile effect on the crystalline lattice. 35 Generally, the lower nanoparticle sizes observed for PuO 2 samples compared to ThO 2 when using similar ring conditions can be attributed to the different mechanisms and temperatures related to the decomposition of oxalate precursors for both the oxides. 52,57 The nanostructure of the oxides obtained by the oxalate route appears to be controlled by the ring temperature and its duration, which involves a loss of nanoscale organization when they both increase.…”
Section: Characterization Of Oxide Nanoparticlesmentioning
confidence: 92%
See 4 more Smart Citations
“…Carbonate and hydroxyl surface groups have been suggested to exhibit a tensile effect on the crystalline lattice. 35 Generally, the lower nanoparticle sizes observed for PuO 2 samples compared to ThO 2 when using similar ring conditions can be attributed to the different mechanisms and temperatures related to the decomposition of oxalate precursors for both the oxides. 52,57 The nanostructure of the oxides obtained by the oxalate route appears to be controlled by the ring temperature and its duration, which involves a loss of nanoscale organization when they both increase.…”
Section: Characterization Of Oxide Nanoparticlesmentioning
confidence: 92%
“…54 The resulting unit cell volume may compress or expand as a function of the material studied. 25,35,54 For instance, an increase in the lattice parameter has been observed for CeO 2 nanoparticles smaller than 20 nm. 55,56 The lattice parameter of a 0 ¼ 5.600(6)Å has been reported for 14 nm ThO 2 particles; 52 Bouexiere et al reported the lattice parameter a 0 of 5.4042(2)Å for 3.7 AE 1.0 nm PuO 2 nanoparticles prepared by hydrothermal 48 Recently, the expansion of the lattice parameter has been observed for ThO 2 nanoparticles that exhibit different sizes.…”
Section: Characterization Of Oxide Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations